O comportamento Fotoquímico dos Complexos Pentaaminas de Rutênio(II) com Ligantes π Insaturados The photochemical behaviour of pentaamineruthenium(ii) complexes with unsaturated π ligands - Rose Maria Carlos (Química Nova, 1997)
A general overview on the photochemical behaviour of [Ru(NH3)5L]2+ complexes (where L is a p ligand) is presented. The proposed mechanisms and techniques employed for the study of these reactions are discussed. Emphasis is made on the mechanisms that allow the identification of the reactive excited state of the [Ru(NH3)5py]2+ complex.